Sustaining growth or boosting profit: Accounting tools under process-based management in a transition economy - Alexey Bobryshev; Lyubov Chaykovskaya; Vasily Erokhin; Anna Ivolga (Journal of Risk and Financial Management, 2023)
Over the past three decades, economic transformations in Eastern Europe and Russia have substantially affected the use of management technologies. More and more businesses prioritize sustaining growth and development in the long run instead of maximizing profits in the short term. The shift in the business paradigm requires the implementation of new management tools along with the improvement of management accounting. Through the example of seven Russian boiler manufacturers, this study examines the main reasons for the transition to process-based management. The study identifies patterns of using management accounting tools in process-based management by employing the literature analysis, conducting an expert survey, and studying the accounting documents of selected companies. The authors analyze features of management accounting tools at different stages of implementation of the process-based management system, in enterprises with different life cycles and different sizes. A total of 53 employees were surveyed, which included senior managers, accountants, and middle-level managers. It is found that the main reason for the transition to process-based management is a shift in the focus of managers' attention from cutting costs to creating value. By adding new features of business process classification, developing new classification groups, and proposing the optimal structure of the core, auxiliary, and controlling business processes, this study contributes to the optimization of management accounting when organizational change requires implementing process-based management.
Keywords: 650; accounting; business processes; costs; economic growth; management accounting; management decision making; process-based management; sustainable growth